(3GdRjfIs - (3CHh MGJe GdQGRj , eMeO Hf GOQjS Hf GdefPQ Hf OGhO Hf egQGf GdMfXj, CHh MGJe,J (B277 (3g` s
(3ChdgG (B:s
(3GdEdMGO(B\(3gh GdGfMQGa Yf GdTF hGdYOhd Yfg hefg , Sei dMO GdbHQ dCfg YOd Yf GdbUO Edi fGMjI ef GdbHQ hMQa MaQg hjbGd deG MaQ ai hSW GdbHQ VQjM s
(3BNQgG (B:s
(3aCeG eG SGFQ Pdc ef CeQ GdCUfGe GdJi cGfJ ddYQH , heG cGf ef CeQ GdejSQ hGdCfUGH hGdCRdGe heG cGf ef Sff eTQci GdYQH abO OQS Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B86 - (3U(B304s
(3HgG BKGQ WeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs